2022
DOI: 10.1002/tox.23627
|View full text |Cite
|
Sign up to set email alerts
|

miR‐219a‐5p inhibits the pyroptosis in knee osteoarthritis by inactivating the NLRP3 signaling via targeting FBXO3

Abstract: Purpose This work was to identify the function and mechanism of miR‐219a‐5p in regulating knee osteoarthritis (KOA). Methods Rat fibroblast‐like synoviocytes (FLSs) were isolated to construct KOA cell model by lipopolysaccharide and adenosine triphosphate treatment. miR‐219a‐5p and FBXO3 expression in FLSs was modulated by transfection. Flow cytometry was executed to research FLSs apoptosis. Caspase‐1 and IL‐1β expression in FLSs was researched by immunofluorescence. The binding between miR‐219a‐5p and FBXO3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…FBXO3 counteracted the effects of miR-215a-5p-inhibited IL-18, IL-1b and pyroptosis-related proteins. Additionally, miR-219a-5p alleviated knee joint injury and elevated step size of rat with knee osteoarthritis partly via inhibition of FBXO3 and inactivation of NLRP3 (45).…”
Section: Fbxo3mentioning
confidence: 94%
See 1 more Smart Citation
“…FBXO3 counteracted the effects of miR-215a-5p-inhibited IL-18, IL-1b and pyroptosis-related proteins. Additionally, miR-219a-5p alleviated knee joint injury and elevated step size of rat with knee osteoarthritis partly via inhibition of FBXO3 and inactivation of NLRP3 (45).…”
Section: Fbxo3mentioning
confidence: 94%
“…This cell model exhibited elevation of IL-18, IL-1b, apoptosis rate, and increased expression of pyroptosis-associated proteins. The abovementioned indicators were downregulated by up-modulation of miR-219a-5p, while downregulation of miR-219a-5p exhibited the opposed results (45). FBXO3 expression was inhibited by miR-219a-5p, and depletion of FBXO3 repressed the expression of IL-18, IL-1b and pyroptosis-related proteins.…”
Section: Fbxo3mentioning
confidence: 94%
“…The down-regulation of miR-219a-5p was observed in FLS affected by OA. Further investigations revealed that miR-219a-5p has the potential to impede the progression of knee OA both in laboratory settings and living organisms by suppressing the expression of F-box protein 3 (FBXO3), thereby inhibiting pyroptosis [ 138 ]. Zhang and colleagues provide evidence that upregulation of HIF-1α in FLS and induction of pyroptosis may cause synovial fibrosis, while inhibition of HIF-1α or GSDMD may improve the marker of FLS fibrosis [ 13 ].…”
Section: Targeting the Pyroptosis For The Treatment Of Oamentioning
confidence: 99%
“…Wang et al also found that miR-219a-5p inhibits pyroptosis in knee osteoarthritis via inactivating the NLRP3 signaling 20 . Chang et al comprehensively analyzed the key genes, signaling pathways and miRNAs of human knee osteoarthritis based on bioinformatics.…”
Section: Introductionmentioning
confidence: 96%